Market protection and tools to contrast mafia enterprises (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
This contribution analyses the evolving features of the mafia enterprise within the rules of the market where it builds economic and contractual relationships with the legal enterprise. In the first part, it reconstructs the role played by the instruments of control of organisational structures envisaged by the Civil Code, as well as by the most recent anti-mafia codes (Legislative Decree no. 159/2011) and the Crisis and Insolvency Code (Legislative Decree no. 14/2019). In the second part, the innovations introduced in the public contracts sector by Legislative Decree No. 36/2023 are examined.
Keywords: Mafia enterprise; economic crime; law enforcement instruments; market protection; market